Penerapan Supervisi Pendidikan Untuk Pencapaian Akreditasi Sekolah - Inom Nasution; Arimbi Syahkila Simangunsong; Elsa Elitia Hasibuan; Lola Amalia Sibarani; Ibnu Qital; Khansa Arista Widya Maulida (Pusat Riset dan Inovasi Nasional, 2023)
This article aims to discuss the application of educational supervision to achieve school accreditation. The research method used in this article is literature study or literature review, where data is obtained by reviewing literature sources. The literature study conducted included the application of educational supervision to achieve school accreditation. The results of this literature study indicate that educational supervision in schools must continue to improve so that school accreditation is even better. We recommend that educational supervision should be carried out properly so as to increase the achievement of school accreditation.